Dampak iklim organisasi terhadap prestasi kerja karyawan dan kepuasan mahasiswa pada Universitas Dr. Soetomo Surabaya - Baruno, Agustiawan Djoko; Sudiro, Djoko (STIE Perbanas Surabaya, 2016)
The purpose of this research is (1) To test and analyze the magnitude of organizational climate impact on employee performance in Dr. Soetomo University Surabaya; (2) To test and analyze the magnitude of the impact of employee performance on student satisfaction at Dr. Soetomo UniversitySurabaya; (3) To examine and analyze the indirect effect of organizational climate on student satisfaction at Dr. Soetomo University Surabaya. This research uses a quantitative approach. The population in this study is all employees and active students of Dr. Soetomo University in even semester Academic Year 2016/2017 from 8 faculties. The taken sample in the research are 100 people from 8 faculties with Proportionate Stratified Random Sampling. The results of this study indicate that (1) Organizational Climate effect on Employee Work Achievement at Dr. University. Soetomo Surabaya, (2) Employee Work Achievement Influence on Student Satisfaction at Dr. Soetomo University Surabaya, (3) Organizational Climate Indirectly Affects Student Satisfaction at Dr. Soetomo University Surabaya. It is expected that the results of the study can provide information and evaluation for the marketing and human resources management department of the Dr. Soetomo university Surabaya.